Economic factors concerning the migration of the best educated workers: The case of college teachers - Antonio Mihi-Ramírez; Yolanda García Rodríguez; Dominik Metelski (Comparative Economic Research. Central and Eastern Europe, 2015)
The migration flow of highly skilled workers is a growing and changing issue, especially under the economic conditions in recent years. This research focused on the migration of university teachers, a highly skilled collective responsible for the training of future skilled workers and also the innovation of a country through their research. An empirical analysis of migration flow of this collective and its relation with economics factor in Europe in the last decade showed that earnings are a key factor explaining variations in the migration flow of university teachers over time. Furthermore, considering the real purchasing power and the effect of personal taxes, it would be possible to show which countries are more relevant to the decisions of this collective on migration. Thus, the higher the purchasing power, the greater the number of university teachers who migrate to a given country. Hence those countries that keep or increase the earnings level of university teachers, especially during an economic depression, can attract or maintain highly skilled workers. In addition, the results showed that unemployment is a push factor for migration for these best educated workers.
Keywords: 330; international migration; economic factors of migration; university teacher's migration; highly skilled workers